Pengaruh Pupuk Trichokompos dan POC-Plus terhadap Pertumbuhan dan Hasil Kacang Hijau (Vigna Radiata L.) di Lahan Kering Sub-optimal - Siti Halisah; Jumar Jumar; Antar Sofyan (Agroekotek View, 2020)
Green beans (Vigna radiata L.) are legume plants that can be developed on sub-optimal dry land which has low nutrient content. Low nutrients can be overcome by giving Trichokompos and POC-plus. Trichokompos and POC-plus are organic fertilizers capable of supporting the growth and productivity of green bean crops on sub-optimal dry land. This study aims to: (1) determine the effect of the interaction of giving Trichokompos and POC-plus on the growth and yield of green bean plants; (2) knowing the best dosage of Trichokompos and POC-plus which can increase the growth and yield of green bean plants; and (3) knowing the POC-plus dose which can increase the growth and yield of green beans on sub-optimal dry land. The study used Random Group (RAK) design two foreign factor, namely Trichocompost (T) which consisted of 3 levels, namely: t0 = 0 t.ha-1 trichokompos; t1 = 5 t.ha-1 trichokompos; t2 = 10 t.ha-1 trichokompos, and POC-plus (P) which consists of 4 levels, namely: p0 = 0 times the POC-plus application; p1 = 2 times the POC-plus application; p2 = 3 times the POC-plus application; p3 = 4 times the POC-plus application. Of these two factors 12 combinations of treatments were obtained with 3 replications, so there were 36 experimental units. The results showed that the interaction between trichokompos and POC-plus did not significantly affect the growth and yield of green beans. However, the single factor trichokompos (T) had a significant effect on plant height and number of poc.